2016
DOI: 10.1136/annrheumdis-2016-eular.4851
|View full text |Cite
|
Sign up to set email alerts
|

FRI0422 Periodontal Disease in Spondyloarthritis Subtypes. Is There A Difference?

Abstract: BackgroundSpondyloarthritis (SpA) are a group of interconnected inflammatory arthritides that include ankylosing spondylitis (AS), reactive arthritis (ReA), and undifferentiated SpA (uSpA). Periodontal disease (PD) is a chronic inflammatory disease that may increase the risk for immune diseases like rheumatoid arthritis and AS.ObjectivesTo evaluate the periodontal condition and presence of Porphyromona gingivalis (P. gingivalis) and P. gingivalis IgG1 and IgG2 antibodies within three subgroups of SpA (AS, uSpA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In contrast, another group found that in 79 spondyloarthropathy patients, of which 19 had AS, levels of insertion loss were lower compared to the control group [89]. The association with P. gingivalis is still not certain, with contrasting findings that antibody titers were higher and lower in AS compared to controls [89,90] Recently, the oral microbiome has been studied in patients with axial spondyloarthritis. Patients were matched for age, gender and ethnicity to healthy controls.…”
Section: Periodontitis and Ankylosing Spondylitismentioning
confidence: 94%
“…In contrast, another group found that in 79 spondyloarthropathy patients, of which 19 had AS, levels of insertion loss were lower compared to the control group [89]. The association with P. gingivalis is still not certain, with contrasting findings that antibody titers were higher and lower in AS compared to controls [89,90] Recently, the oral microbiome has been studied in patients with axial spondyloarthritis. Patients were matched for age, gender and ethnicity to healthy controls.…”
Section: Periodontitis and Ankylosing Spondylitismentioning
confidence: 94%